2013
DOI: 10.1007/s11910-013-0414-8
|View full text |Cite
|
Sign up to set email alerts
|

Update on Herpes Virus Infections of the Nervous System

Abstract: Herpes simplex viruses types 1 and 2 (HSV-1 and HSV-2) are human neurotropic viruses that establish latent infection in dorsal root ganglia (DRG) for the entire life of the host. From the DRG they can reactivate to cause human morbidity and mortality. Although they vary, in part, in the clinical disorders they cause, and in their molecular structure, they share several features that govern the biology of their infection of the human nervous system. HSV-1 is the causative agent of encephalitis, corneal blindnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
119
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 90 publications
0
119
0
6
Order By: Relevance
“…The virus uses multiple receptors for successful infection in a variety of cell types, including MEFs. Studies in animal models and in humans have shown that HSV-1 infection is not only the major cause of severe herpes infections on the mouth and lips, but also an important cause of fatal sporadic encephalitis (25,26). In the current study, we report that HSV-1 infection triggers RIP3/MLKL-dependent necrosis via an RHIMcontaining viral ribonucleotide reductase large subunit (ICP6).…”
mentioning
confidence: 64%
“…The virus uses multiple receptors for successful infection in a variety of cell types, including MEFs. Studies in animal models and in humans have shown that HSV-1 infection is not only the major cause of severe herpes infections on the mouth and lips, but also an important cause of fatal sporadic encephalitis (25,26). In the current study, we report that HSV-1 infection triggers RIP3/MLKL-dependent necrosis via an RHIMcontaining viral ribonucleotide reductase large subunit (ICP6).…”
mentioning
confidence: 64%
“…The mortality of untreated HSV encephalitis is roughly 70 %, and 97 % of survivors will not return to their previous level of function [41,[154][155][156]. Clinical trials in the 1980s demons t r a t e d s i g n i f i c a n t l y i m p r o v e d o u t c o m e s w i t h intravenous aciclovir, as described above [103,104], and the 1-year mortality with current antivirals and supportive care is now in the range of 5-15 %, despite high rates of admission to the ICU [44,60,157].…”
Section: Discussionmentioning
confidence: 99%
“…A survey from 2005 to 2010 including Americans between 14 and 49 years of age in the USA estimated HSV-1 seropositivity at 54 % and HSV-2 seropositivity at~16 % [40]. While HSV-2 is also capable of causing encephalitis (particularly in the immunocompromised host), HSV-1 is responsible for~90 % of HSV encephalitis in adults and children, and is the focus of this review [41]. Despite only rarely manifesting as encephalitis in infected individuals, HSV-1 is consistently the single most common cause of sporadic encephalitis worldwide [42][43][44][45][46][47][48][49][50][51][52].…”
Section: Epidemiologymentioning
confidence: 99%
“…HSE is the most common sporadic viral encephalitis in the Western world. This life-threatening disease strikes otherwise healthy children once (recurrence is rare) in the course of primary infection with the herpes simplex virus, which is ubiquitous and typically innocuous (111). The arguments against a genetic hypothesis and against a monogenic hypothesis in particular included the sporadic nature of the disease, with only four multiplex families having been reported since its first description in 1941 (112).…”
Section: Hse: a Model Diseasementioning
confidence: 99%